2018
DOI: 10.1380/ejssnt.2018.201
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Organics on Substrates with Metallic Surface States: Why?, So??

Abstract: This paper modestly expands an invited talk at ISSS-8 with the same title. After reviewing the relevant interactions between adsorbates on substrates with metallic surface states [especially Cu(111)], it focuses on organic adsorbates. Of particular interest are those which form honeycomb lattices with pores of various sizes. The nature of the confined states derived from the surface-state electrons is discussed as their effect on admolecules inside the pores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Simulations for this system concluded that the first and second confined states (in that order) drive the CO adsorption positions (Cheng et al, 2010), whereby CO molecules seize adsorption sites with high LDOSs. Therefore, the diffusion is limited not only by the physical barriers (molecules) but also by the modified LDOS generated by the QD array (Einstein, Bartels, and Morales-Cifuentes, 2018).…”
Section: B Guided Adsorption Of Adatoms and Simple Molecules In Qd Ar...mentioning
confidence: 99%
“…Simulations for this system concluded that the first and second confined states (in that order) drive the CO adsorption positions (Cheng et al, 2010), whereby CO molecules seize adsorption sites with high LDOSs. Therefore, the diffusion is limited not only by the physical barriers (molecules) but also by the modified LDOS generated by the QD array (Einstein, Bartels, and Morales-Cifuentes, 2018).…”
Section: B Guided Adsorption Of Adatoms and Simple Molecules In Qd Ar...mentioning
confidence: 99%